The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1055/s-0040-1718959
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Benefit of Bone Anchored Hearing Systems: Behavioral Performance and Self-Reported Outcomes

Abstract: Introduction Bone anchored hearing solutions are a well-known option for patients with a conductive, mixed conductive-sensorineural hearing loss and those with single-sided deafness. Objective The aim of the present study was to evaluate the Ponto bone-anchored hearing system in terms of behavioral performance and self-reported outcomes, by comparing unaided and aided performance (softband and abutment), as well as aided performance with the sound processor on softband (preoperatively) versus abutmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Other studies ( Kunst et al 2008 ; Bosman et al 2018 ; Cuda et al 2021 ; Bosman et al 2021 ) collected SSQ49 scores using a group of adult users—most of which were unilaterally implanted. The scores obtained by Bosman et al (2018 ) for the spatial factor of the SSQ49 ( Akeroyd et al 2014 ) were very similar to those obtained here (2.6 with an older sound processor and 3.9 with a newer superpower sound processor; 67% of the listeners were unilaterally fitted), as well as the SSQ49 scores obtained in the spatial scale by Cuda et al (2021 ) for a group of unilaterally fitted BAHS users (average score of 4.2). Kunst et al (2008 ) and Bosman et al (2021 ) reported higher mean scores for unilaterally fitted adult BAHS users, 6.8 and 5.1 in the spatial scale, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies ( Kunst et al 2008 ; Bosman et al 2018 ; Cuda et al 2021 ; Bosman et al 2021 ) collected SSQ49 scores using a group of adult users—most of which were unilaterally implanted. The scores obtained by Bosman et al (2018 ) for the spatial factor of the SSQ49 ( Akeroyd et al 2014 ) were very similar to those obtained here (2.6 with an older sound processor and 3.9 with a newer superpower sound processor; 67% of the listeners were unilaterally fitted), as well as the SSQ49 scores obtained in the spatial scale by Cuda et al (2021 ) for a group of unilaterally fitted BAHS users (average score of 4.2). Kunst et al (2008 ) and Bosman et al (2021 ) reported higher mean scores for unilaterally fitted adult BAHS users, 6.8 and 5.1 in the spatial scale, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Caspers et al (2022) also collected SSQ scores on bilaterally implanted BAHS users (adults) but the data were not reported. Other studies (Kunst et al 2008; Bosman et al 2018; Cuda et al 2021; Bosman et al 2021) collected SSQ49 scores using a group of adult users—most of which were unilaterally implanted. The scores obtained by Bosman et al (2018) for the spatial factor of the SSQ49 (Akeroyd et al 2014) were very similar to those obtained here (2.6 with an older sound processor and 3.9 with a newer superpower sound processor; 67% of the listeners were unilaterally fitted), as well as the SSQ49 scores obtained in the spatial scale by Cuda et al (2021) for a group of unilaterally fitted BAHS users (average score of 4.2).…”
Section: Discussionmentioning
confidence: 99%